Pengaruh Love Of Money, FOMO Dan Pengendalian Diri Terhadap Pengelolaan Keuangan Dengan Literasi Keuangan Sebagai Variabel Moderasi Pada Ibu Rumah Tangga Di Gumuksari Jember - Elvira Oktafia (FAKULTAS EKONOMI DAN BISNIS, 2025)
This study aims to examine the influence of Love of Money, Fear of Missing Out (FOMO), and Self-Control on Financial Management, with Financial Literacy as a moderating variable among housewives in Gumuksari Village, Kalisat District, Jember Regency. This research uses a quantitative approach with a survey method through the distribution of questionnaires. The number of samples used in this study was 105 respondents selected using purposive sampling. Data analysis was carried out using the Structural Equation Modeling–Partial Least Square (SEM–PLS) method with the help of SmartPLS 4.0 software. The results of this study indicate that: (1) Love of Money does not have a significant effect on financial management; (2) FOMO does not have a significant effect on financial management; (3) Self Control has a significant effect on financial management; (4) Financial Literacy significantly moderates and weakens the influence of Love of Money on financial management; (5) Financial Literacy does not moderate the relationship between FOMO and financial management; and (6) Financial Literacy significantly moderates and weakens the effect of Self-Control on financial management. These findings highlight the importance of financial literacy in shaping rational financial behavior and show that psychological factors need to be supported by adequate financial knowledge to achieve more effective financial management.
Reuploud Repository hasyim Mei 2026 Validasi dan Finalisasi Repositori File 18 Juni 2026_Kholif Basri
Keywords: Love of Money; FOMO; Self-Control; Financial Literacy; Financial Management.